Eristalis (Eoseristalis) arbustorum - El-Hawagry, Magdi S.; Gilbert, Francis (Zenodo, 2019)
Eristalis ( Eoseristalis ) arbustorum (Linnaeus, 1758) Musca arbustorum Linnaeus, 1758: 591. Type locality: Sweden. Material examined : 1 female, St. Katherine, Sinai, 4.VII.2012, leg. Norfolk [unpublished thesis of Norfolk (2015)]. World distribution : NE: Wisconsin to Labrador, s. to Kansas & South Carolina. OR: India. PA: Algeria, Egypt, Europe (Fennoscandia southwards; from Ireland eastwards through much of Europe into Russia and on through Siberia to the Pacific coast (Sakhalin)), Morocco, Tunisia. Egyptian localities : Sinai: St. Catherine. Activity period in Egypt : July. Remarks : Norfolk (2015) found a female specimen of Eristalis arbustorum (L.) in St. Catherine, Sinai visiting Achillea fragrantissima . Published as part of El-Hawagry, Magdi S. & Gilbert, Francis, 2019, Catalogue of the Syrphidae of Egypt (Diptera), pp. 201-248 in Zootaxa 4577 (2) on page 222, DOI:10.11646/zootaxa.4577.2.1, http://zenodo.org/record/2629643